Planejamento territorial em Feira de Santana (BA): urbanização e requalificação da Lagoa do Subaé - Aguilar, Caio Macieira de Almeida (2021)
This work has as its theme territorial planning with emphasis on urbanization projects and urban requalification. In this context, as a general objective, an infrastructure and urbanism project was elaborated for Lagoa do Subaé in Feira de Santana based on integrated urban territorial planning. To support this proposition, we sought to understand the dynamics and urban evolution of the study area from its surroundings, delimiting the Permanent Preservation Area (APP). Soil use and occupation were mapped, a digital database of priority areas for intervention was created and the modeling of soil waterproofing around the lagoon was performed before and after the intervention planned in the project. As a methodology, in addition to the literature review and documentary analysis, the proposed modeling was made based on the use of a Digital Terrain Model obtained through the use of Unmanned Aerial Vehicle, as well as maps of classification of land use and slope, as well as, using Geographic Information Systems, a digital database associated with the interpretation of indices and indicators generated from the collected data was created. The proposed urban requalification project was elaborated in Trimble's SketchUp software. The results of this proposal allow us to affirm the feasibility of the proposed project, based on fundraising instruments commonly used in projects of this size and the subdivision of the proposal into stages. In addition, the proposal presented here has great potential to ensure the environmental recovery of an intensely degraded area, with positive impacts on the health and quality of life of the population living in the surroundings and for the other inhabitants of the city of Feira de Santana. The main challenge is the relocation of inhabitants whose residences are within the perimeter of the APP, which has already been carried out in another lagoon requalification project in the city.